ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN GIZI SEIMBANG PADA TATANAN RUMAH TANGGA DI DESA SEI KAMAH I KEC. SEI DADAP KABUPATEN ASAHAN TAHUN 2023 - lubis, fitri handayani; Sembiring, Bungamari (Jurnal Penelitian Kesmasy, 2024)
Preliminary survey data shows that housewives have not implemented a balanced nutrition program in the household setting, such as consuming a variety of foods, reducing salt and sugar and some even rarely consuming vegetables and fruit. The type of research used is Quantitative Research using a Cross-Sectional approach which aims to analyze factors related to the implementation of balanced nutrition in household settings in Sei Kamah I Village, Kec. Sei Dadap Asahan District. The time of the research starts from November 2022 to June 2023. The population in this study are all housewives who live in Sei Kamah I Village, Kec. Sei Dadap Asahan Regency numbered 695 people. The sample size is calculated using the minimum sample formula from Lemeshow, so that a minimum sample size of 150 people is obtained. All variables in this study are related to the implementation of balanced nutrition in the household setting and attitude is the most related variable and the positive attitude of housewives has a 3,554 times chance of increasing the application of balanced nutrition in the household setting in Sei Kamah I Village, Kec. Sei Dadap Asahan District. It is hoped that village organizers will be able to collaborate with health centers and other cross-sectors to carry out routine education for housewives regarding the implementation of balanced nutrition in the household order to increase knowledge which will directly influence the attitude of housewives to be more positive in implementing nutrition. balanced and the Public Health Center to carry out periodic and routine monitoring related to non-communicable disease visits and provide assistance in implementing balanced nutrition in the household setting for these residents.